Vehicular Pollution in Katmandu Valley - Sapkota, Ramchandra (Journal of the Institute of Engineering, 2011)
This paper highlights the issue of vehicular pollution in the Kathmandu valley. Vehicular pollutants include CO, HC, NOx, Sox, lead and particulate matters which have damaging effects on both human health and ecology. Diesel-driven vehicles emit particulates that are very fine and a large proportion of them are less than 2.5 microns in size, which can penetrate deeper into our lungs. These pollutants are believed to affect the respiratory and cardiovascular systems. Uncontrolled growth of vehicle population, poor transportation infrastructure, traffic congestion, driving patterns and inefficient public transportation systems are major factors in increasing vehicular pollution levels. Key words: Vehicular pollution; Vehicle population; Pollutants; Transportation infrastructure; PM2.5. DOI: http://dx.doi.org/10.3126/jie.v8i1-2.5106 Journal of the Institute of Engineering Vol. 8, No. 1&2, 2010/2011 Page: 149-152 Uploaded Date: 20 July, 2011